Analisis Kebijakan Monopoli Dan Persaingan Bisnis Dalam Sektor Transportasi: Kasus Pt. Kereta Api Indonesia - Titha Valencia Nurrahmawati; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The study examines the implications of monopolies and market competition within the context of Indonesian railways PT. Kereta Api Indonesia (KAI). The analysis highlights the challenges posed by monopolistic practices in PT. KAI, including their impact on consumer welfare, market dynamics, and economy equity. The researcg objectives include analyzing the legal framework governing monopolies, assessing market competition dynamics, and evaluating the regulatory challenges in promoting for competition. The study employs a combination of legal-normative and empirical approaches, including case studies to explore these issues. The findings reveal that while state-owned enterprises (BUMN) are granted exemptions under Law No. 5 of 1999 to engage in monopolistic practices for national interests, such practices can still lead to market inefficiencies and hinder competition. The study also identifies the need for enchanced regulatory mechanisms to ensure fire market conditions and protect consumer rights. Additionally, the research underscores the importance of balancing states interest with competitive market dynamics to achieve sustainable economic growth.